Hubungan Kepatuhan Pembatasan Cairan Terhadap Terjadinya Overload Cairan pada Pasien Gagal Ginjal Kronik Post Hemodialisa di RSUD DR. HI. Abdul Moeloek Provinsi Lampung - Budiarti Budiarti; Rika Yulendasari; Eka Yudha Chrisanto (Universitas Malahayati Lampung, 2023)
ABSTRACT Chronic kidney failure is a health problem in the world that continues to increase. According to data from the World Health Organization (WHO) chronic kidney disease kills 850,000 people every year. RSUD Dr. Hi. Abdul Moeloek, Lampung Province, based on medical record data, it is known that the number of CRF sufferers in 2022 is 17,939 sufferers. Limiting intake of fluids and electrolytes in patients with chronic kidney failure (CKD) is very important. To know the relationship between compliance with fluid restrictions and the occurrence of fluid overload in post-hemodialysis chronic kidney failure patients at RSUD Dr. Hi. Abdul Moeloek Lampung Province in 2023.The type of research used in this research is quantitative. The design in this study uses analytic with a cross-sectional approach. The population of this study were post hemodialysis chronic kidney failure patients at RSUD Dr. Hi. Abdul Moeloek Lampung Province in 2023 a total of 159 people, with a sample of 114 respondents. Data collection used a checklist sheet and a statistical test questionnaire using the chi square test. The level of adherence to fluid restriction in patients with chronic kidney failure showed that out of 114 respondents, the majority, namely 68 respondents (59.6%), were in the non-adherent category. The incidence of fluid overload in patients with chronic kidney failure showed that almost half of the respondents did not experience fluid overload, namely 23 respondents (40.4%). From the analysis between the two variables, it is known that there is a significant relationship between adherence to fluid restrictions and the occurrence of hypervolemia in chronic kidney failure patients at RSUD Dr. Hi. Abdul Moeloek Lampung Province with p value = 0.011 (p value 0.000 0.05). Nurses in the hemodialysis room are expected to be more active in providing guidance or health education about diet and fluid intake in patients with chronic kidney failure undergoing hemodialysis so that the expected results are maximized. Keywords: Compliance,Fluid Restriction, Fluid Overload, Chronic Renal Failure ABSTRAK Gagal ginjal kronis menjadi masalah kesehatan di dunia yang terus mengalami peningkatan. Menurut data World Health Organization (WHO) penyakit ginjal kronis membunuh 850.000 orang setiap tahun. RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung, berdasarkan data rekam medis diketahui bahwa jumlah penderita GGK pada tahun 2022 sejumlah 17.939 penderita. Pembatasan asupan pada cairan dan elektrolit pada pasien penderita gagal ginjal kronik (GGK) sangatlah penting. Diketahui Hubungan Kepatuhan Pembatasan Cairan Terhadap Terjadinya Overload Cairan Pada Pasien Gagal Ginjal Kronik Post Hemodialisa Di RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung Tahun 2023. Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif. Rancangan dalam penelitian ini menggunakan analitik dengan menggunakan pendekatan croos sectional. Populasi penelitian ini adalah pasien gagal ginjal kronik post hemodialisa di RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung Tahun 2023 sejumlah 159 orang, dengan sampel 114 responden. Pengumpulan data menggunakan lembar checklist dan kuesioner uji statistic menggunakan uji chi square. Tingkat kepatuhan pembatasan cairan pada pasien gagal ginjal kronik didapatkan hasil bahwa dari 114 responden sebagian besar yaitu 68 responden (59,6%) termasuk kategori tidak patuh. Kejadian overload cairan pada pasien gagal ginjal kronik didapatkan hasil hampir setengah dari responden tidak mengalami overload cairan yaitu sebanyak 23 responden (40,4%). Dari analisis antara kedua variabel diketahui bahwa ada hubungan yang bermakna antara kepatuhan pembatasan cairan terhadap terjadinya hipervolemia pada pasien gagal ginjal kronik di RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung dengan p value = 0,011 (nilai p 0,000 0,05). Perawat diruangan hemodialisa diharapkan lebih aktif lagi dalam memberikan bimbingan ataupun penyuluhan kesehatan tentang asupan diet dan cairan pada pasien gagal ginjal kronik yang menjalani hemodialisa agar hasil yang diharapkan lebih maksimal. Kata Kunci: Kepatuhan, Pembatasan Cairan, Kelebihan Cairan, Gagal Ginja Kronis